The Edupreneur: Empowering Education through Entrepreneurial Innovation - Carmen-Liliana Maruntelu (Ovidius University Annals: Economic Sciences Series, 2023)
This paper examines the concept of edupreneurship and its impact on the education system. Edupreneurship is an innovative approach that combines elements of entrepreneurship and education, aiming to transform and improve the learning process. The paper highlights the main characteristics of edupreneurship, including initiative, creativity, risk-taking and entrepreneurship. The benefits of edupreneurship in terms of developing key 21st century skills such as critical thinking, problem solving and collaboration are also analysed. A relevant case study is also presented, illustrating how edupreneurs are contributing to the transformation of education systems in Romania. The paper highlights the importance of support and collaboration between education, business and government to promote edupreneurship. By implementing edupreneurship, we can create an educational system adapted to the needs of society and prepared for the challenges of the future.